Environmentally sound management of health care waste in the kathmandu valley. - Shrestha, Gyan Kumar Chhipi (2005)
SUMMARY: Health care waste are those wastes which are generated in the diagnosis treatment or immunization of human beings or animals. These wastes are multi-hazard waste constituting infectious, radiological, chemical or physical hazards. In the hospitals about 20-25% wastes are hazardous. When they are not segregated properly they contaminate other non-hazardous waste too making all the waste hazardous. " Environmentally sound management of Health Care Waste (HCW) in the Kathmandu Valley" is studied by taking to sample hospitals including public & private hospitals in Kathmandu. Lalitpur and Bhaktapur districts. A pre-designed questionnaire is used to take the necessary data about the HCV in the respective hospitals. Similarly, observation is made for different aspects of HGW Management in hospitals. The results shows that HCW is not managed properly in the hospitals in the Kathmandu Valley. There is a lack of proper segreagation of HCW. In some hospitals although the wastes are segregated, they are mixed during the final disposal. Moreover, the simple burning or combustion in incinerator without controlled emission is producing dioxins, mercury particles, NOx, Sox, and also the Hydrochloride gas. Similarly, the unsafe burial of wastes specially the pathological waste is polluting the soil and ground water. The haphazard disposal of mercury thermometers is creating mercury pollution in air, water, and soil effecting the biota including human. The proper HCW management requires costs than between nothing. So, a better way is to frame "Health Care Waste Management Rules" under Environment in hospitals. It would be better to segregate HCW into six categories such as i) Organic waste IV) Infectious non-PVC material II) Inorganic waste V) Infectious PVC materials III) Sharps VI) Chemicals and radioactive wasted However if hydroclave is used, It can segregated in 5 categories by combing category IV and V. Further Kathmandu Valley/ Central treatment Facility is better. So, Central Hydroclave or Central Autoclave with emission controlled Incinerator is better. The burning of PVC materials should be stopped soon. The PVC materials till. The burning of PVC materials should be stopped soon. The PVC materials Till the management of the Hydroclave or Autoclave or other treatment facility should be treated with chemical disinfectants and then buried in Safe Burial Pit. Similarly, the waste category III (Sharps), Category IV (Infectious waste non-PVC materials) and Category VI (Chemicals including thermometer) should be buried in the Safe Burial Pit after treating with chemical disinfectants in the landfill sites. Finally, the Environmentally sound management of HCW can be achieved effectively with the legal provision and growing awareness among the general public and hospital administrators.